2015
DOI: 10.1016/j.pmrj.2015.06.440
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Rehabilitation: Do Functional Gains Relate to 60 Percent Rule Classification or to the Presence of Metastasis?

Abstract: Patients with functional limitations resulting from cancer or its treatment made significant functional gains in inpatient rehabilitation. There were no significant differences in functional gains made by those with or without metastatic disease or those compliant versus noncompliant with the 60% rule. The presence of metastatic disease or a diagnosis not compliant with the 60% rule does not preclude cancer patients from making significant functional gains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…Although patients with advanced cancer may utilize inpatient rehabilitation more than those with controlled disease [38], Sliwa et al found that patients with metastases benefitted from inpatient rehabilitation similarly to patients without metastatic or advanced disease, regardless of the presence of common inpatient rehabilitation diagnoses such as spinal cord injury (SCI), stroke, or neuromuscular disease [39••]. Furthermore, patients with impairments such as SCI due to tumor compression have been shown to benefit from inpatient rehabilitation [40].…”
Section: Introductionmentioning
confidence: 99%
“…Although patients with advanced cancer may utilize inpatient rehabilitation more than those with controlled disease [38], Sliwa et al found that patients with metastases benefitted from inpatient rehabilitation similarly to patients without metastatic or advanced disease, regardless of the presence of common inpatient rehabilitation diagnoses such as spinal cord injury (SCI), stroke, or neuromuscular disease [39••]. Furthermore, patients with impairments such as SCI due to tumor compression have been shown to benefit from inpatient rehabilitation [40].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Guo et al [8] was able to demonstrate that asthenic (a non‐60% rule compliant diagnosis) patients with cancer are able to make statistically significant functional improvements on inpatient rehabilitation. A study by Sliwa et al [9] revealed no significant differences in functional gains made by patients with cancer with diagnoses that were 60% rule compliant versus 60% rule noncompliant. However, institutions also must be aware of the ability to use the remaining 40% of admissions for “noncompliant” diagnoses.…”
Section: Regulatory Considerationsmentioning
confidence: 96%
“…Alam et al [61] reported a statistically significant difference of unplanned transfers back to the primary acute care service of 21% of patients with cancer in the IRF versus 9.7% of noncancer‐matched controls. Other studies have reported return to the primary acute care service rates of IRF patients with general cancers between 16.5% and 35% [9,20,21,66‐68]. In most cases, an uninterrupted acute inpatient rehabilitation course with discharge home is considered a successful IRF admission [69,70].…”
Section: Medical Fragilitymentioning
confidence: 99%
“…Rehabilitation can be incredibly effective in improving cancer patients' function, even in the context of advanced disease . In fact, rehabilitation at the end of life has been shown to reduce the amount of unmet needs at death and lead to lower resource utilization among hospice patients .…”
Section: Futility In Cancer Rehabilitation In Patients With Terminal mentioning
confidence: 99%